Intrathecal delivery of mesenchymal stromal cells protects the structure of altered perineuronal nets in SOD1 rats and amends the course of ALS - Forostyak, Serhiy; Homola, Ales; Turnovcova, Karolina; Svitil, Pavel; Jendelova, Pavla; Sykova, Eva (Stem cells, 2014)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disorder resulting in a lethal outcome. We studied changes in ventral horn perineuronal nets (PNNs) of superoxide dismutase 1 (SOD1) rats during the normal disease course and after the intrathecal application (5 × 10(5) cells) of human bone marrow mesenchymal stromal cells (MSCs) postsymptom manifestation. We found that MSCs ameliorated disease progression, significantly improved motor activity, and prolonged survival. For the first time, we report that SOD1 rats have an abnormal disorganized PNN structure around the spinal motoneurons and give different expression profiles of chondroitin sulfate proteoglycans (CSPGs), such as versican, aggrecan, and phosphacan, but not link protein-1. Additionally, SOD1 rats had different profiles for CSPG gene expression (Versican, Hapln1, Neurocan, and Tenascin-R), whereas Aggrecan and Brevican profiles remained unchanged. The application of MSCs preserved PNN structure, accompanied by better survival of motorneurons. We measured the concentration of cytokines (IL-1α, MCP-1, TNF-α, GM-CSF, IL-4, and IFN-γ) in the rats' cerebrospinal fluid and found significantly higher concentrations of IL-1α and MCP-1. Our results show that PNN and cytokine homeostasis are altered in the SOD1 rat model of ALS. These changes could potentially serve as biological markers for the diagnosis, assessment of treatment efficacy, and prognosis of ALS. We also show that the administration of human MSCs is a safe procedure that delays the loss of motor function and increases the overall survival of symptomatic ALS animals, by remodeling the recipients' pattern of gene expression and having neuroprotective and immunomodulatory effects.
Keywords: krysa rodu Rattus; Granulocyte-Macrophage Colony-Stimulating Factor; chondroitinsulfát proteoglykany; Amyotrophic Lateral Sclerosis; neurony; Extracellular Matrix; Rats; Cell Differentiation; nervová síť; mužské pohlaví; mícha; Mesenchymal Stem Cells; Neurons; TNF-alfa; faktor stimulující granulocyto-makrofágové kolonie; buněčná diferenciace; extracelulární matrix; Male; amyotrofická laterální skleróza; Spinal Cord; mezenchymální kmenové buňky; Animals; Chondroitin Sulfate Proteoglycans; Tumor Necrosis Factor-alpha; zvířata; Nerve Net